FREQUENCY OF NEONATAL SEPSIS AMONG NEONATES PRESENTING WITH SEIZURES - Imran, Abid; Rehman, Sijad-Ur-; Qadir, Imran; Sheikh, Kainaat; Bibi, Romana; Idrees, Muhammad (Journal of Rawalpindi Medical College, 2023)
BACKGROUND: Neonatal seizures may be the first and sometimes the only clinical symptom of neonatal central nervous system disease. Neonatal seizures may indicate an underlying treatable cause. Therefore, the identification of neonatal seizures is important in the management of high-risk newborns. OBJECTIVE: To determine the frequency of neonatal sepsis among neonates presenting with seizures. Settings: Department of child health, Hayatabad Medical Complex, Peshawar. Duration: 6 months 13/10/2018 to 13/4/2019. Study Design: Descriptive (cross sectional) study. MATERIAL AND METHODS: In this study a total of 195 patients were observed. All neonates were subjected to detailed clinical examination like general physical, neurological examination and detail systemic examination and complete set of baseline investigations. From all neonates, 5cc of venous blood was obtained under strict aseptic technique and was sent to hospital laboratory for measuring the TLC, Absolute neutrophil count, CRP and platelet count to confirm the presence or absence of neonatal sepsis. RESULTS: In this study mean age was 10 days with standard deviation ±8.36. Fifty eight percent neonates were male while 42% neonates were female. More over the 42% neonates had neonatal sepsis while 58% neonates didn’t had neonatal sepsis. CONCLUSION: Our study concludes that the frequency of neonatal sepsis was 42% among neonates presenting with seizures.